PENEGAKAN HUKUM TERHADAP TUKANG TULIS TOGEL DALAM TINDAK PIDANA PERJUDIAN JENIS TOGEL DI KABUPATEN KARO SUMATERA UTARA - Rocky Handika Tarigan; Dessy Artina; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Gambling crimes are often found in various community environments Karo District. The essence is contrary to religion, morality and morality of Pancasila and dangerous society, nation and state and in terms of national interests. The type of gambling that is widely traded in Karo Regency is the type of Singapore Togel gambling and Hong Kong Togel (Tolam). Hoping that Togel's sales activities are profitable business activities. Every Writeer gets 15% (fifteen percent) of sales turnover for one round. The author intends to discuss the arrest of the Togel Writeman who is still selective. And the bandarundur was also never arrested by law enforcement officials. The purpose of this study was to study law enforcement carried out by law enforcers against the Togel Writeers in Karo District and violations in the enforcement and eradication of types of lottery crime in Karo District.This research was conducted in North Sumatra Karo District, which conducted research on the Tanah Karo Resort Police, Kabanjahe District Court and Kede Kopi (coffee shop) located in the Karo Regency area. The technique used in collecting data is observation, interview and literature study.From the results of the study, it can be concluded first, the implementation of law enforcement and eradication of scribes in the criminal acts of gambling types in the Karo Regency are carried out by law enforcement officials including preventive and repressive actions. Preventive and refresive law enforcement cannot be carried out maximally. The implementation of law enforcement on law enforcement for law enforcement officers is still selective. And there has not been a specific effort from law enforcement officials to provide the lottery gambling. In law enforcement by the Tanah Karo Resort Police are still focused on the existence of reports directly from the public. And second, the obstacles in the enforcement and eradication of criminal acts of gambling in the North Sumatra Karo Regency consist of two factors, namely internal factors and external factors. Internal factors are the inhibiting factors that come from within the body of law enforcement officers, namely from the Tanah Karo Resort Police Agency which consists of: constraints to law enforcement, constraints on facilities and infrastructure, professionalism of law enforcement officers, low knowledge of law enforcement officers. And external factors are inhibiting factors that come from outside the body of the Tanah Karo Resort Police, which include: a network of organized gambling syndicates, the presence of persons who protect the circulation of criminal gambling gambling, community constraints, regulatory constraints.Keywords: Law Enforcement-Crime-Gambling-Togel